Evaluation of different strategies to mask boar taint in cooked sausage. (June 2016) - Martínez, B.; Rubio, B.; Viera, C.; Linares, M.B.; Egea, M.; Panella-Riera, N.; Garrido, M.D.
Abstract: The use of smoking and/or spices was evaluated for their ability to mask boar taint in frankfurters manufactured from entire pigs with high levels of androstenone. Five frankfurter types were considered: control, smoked, flavouring + smoked, spicy and spicy + smoked. A trained panel in androstenone perception carried out a sensory profile on the different sausages. The highest scores for androstenone perception (odour, flavour and aftertaste) were found in frankfurters that included no masking strategy which indicated the effectiveness of the evaluated strategies. Regarding masking strategies, the contribution of spices and smoking to sensory perception of frankfurters was detected by the panellists. Smoking was the best strategy to mask androstenone odour, while the use of spices masked androstenone odour to a greater extent than androstenone flavour. Only the combined use of spices and smoking was able to eliminate the perception of androstenone. The application of this strategy in frankfurters could be an alternative in the commercialization of entire pigs.